1975
DOI: 10.1152/jappl.1975.38.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Inherited susceptibility of cattle to high-altitude pulmonary hypertension

Abstract: This study examines the hypothesis that susceptibility of cattle to high-altitude pulmonary hypertension and heart failure (high mountain disease) is genetically transmitted. Eight offspring of cattle recovered from high mountain disease were considered "susceptible." Eleven offspring of healthy cattle residing at high altitude were considered "resistant." At the resident altitude of 1,524 m, 10-day-old susceptible calves had higher pulmonary arterial pressures than did resistant calves (34 vs.21 mmHg), but at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 0 publications
0
27
1
1
Order By: Relevance
“…It was previously documented that some subjects are more susceptible (high responders) to the development of pulmonary hypertension in hypoxic conditions than others (nonresponders) [22,23]. However, in the present study no significant correlations were found between diurnal vascular response to hypoxia and hypercapnia, daytime Ppa and the slope of Ppa changes during the night.…”
Section: Discussioncontrasting
confidence: 84%
“…It was previously documented that some subjects are more susceptible (high responders) to the development of pulmonary hypertension in hypoxic conditions than others (nonresponders) [22,23]. However, in the present study no significant correlations were found between diurnal vascular response to hypoxia and hypercapnia, daytime Ppa and the slope of Ppa changes during the night.…”
Section: Discussioncontrasting
confidence: 84%
“…Sakai et al (26) studied the differences in pulmonary hemodynamic characteristics between pikas (genus Ochotona), as high-altitude-adapted animals, and Wistar rats. They clearly demonstrated that significantly lower values of Ppa, PVR, and the ratio of right to left ventricular weight were observed in pikas than in rats at various altitudes of 4,460, 3,300, 2,300, and 610 m. Will et al (35) and Weir et al (33) demonstrated that offspring of cattle that were found to be either susceptible or resistant to the development of ''brisket disease'' retained their respective susceptible or resistant trait for at least two generations. These reports suggest that the differences in pulmonary vascular responses to high altitude between highland natives and lowlanders could be attributable to genetic adaptation.…”
Section: Exercise Performance Of Tibetan and Han Adolescentsmentioning
confidence: 96%
“…The studies that support the hypothesis that pulmonary adaptative responses to high altitude are determined by environmental and/or developmental factors 665 EXERCISE PERFORMANCE OF TIBETAN AND HAN ADOLESCENTS (2,4,6,10,11,19,22) seem to argue against the presumptions that are in accord with the genetic hypothesis implication (3,9,16,26,33,35). It could be proposed, however, that the mechanisms responsible for the process of pulmonary adaptation to highaltitude environment may include both considerations.…”
Section: Exercise Performance Of Tibetan and Han Adolescentsmentioning
confidence: 98%
“…Los valores de PAPm obtenidos en la altura (Cuadro 1) estuvieron elevados y similares a los obtenidos por Tucker et al (1975) y Will et al (1975) en condiciones similares. Para Ames (2001), estos valores de PAPm están dentro del rango aceptable para introducir ganado bovino en la altura (PAPm < 41 mm Hg) pudiendo considerarse como un buen indicador.…”
Section: Discussionunclassified